The Impact of the Islam and Religious Moderation Course on Students’ Moderate Behaviour: The Mediating Role of Attitude in Islamic Higher Education - Fahrurrozi Fahrurrozi; Mustaqim Mustaqim; Lulut Dwi Ratna; Sirojul Fuad; Mustopa Mustopa (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study examines the impact of religious moderation course services—namely course materials, learning strategies, and learning environment—on students' moderate behaviour, mediated by their attitudes. The research was conducted at UIN Walisongo with a sample of 215 students who had taken the course